KINEMATIC DESIGN AS A MEANS OF SPECIFYING THE COORDINATES OF ENEMY UAVS - AFTANAZIV, IVAN; SHEVCHUK, LILIA; STRUTYNSKA, LESYA; STROGAN, ORYCA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The purpose of the work is to increase the defense capability of military units, populated areas of Ukraine and their infrastructure by resisting attacks by attack and sabotage reconnaissance unmanned aerial vehicles (UAVs). Its main result is the creation of a methodology for determining the coordinates, velocities and trajectories of spatial movements of moving objects by means of kinematic design and the development of principle schemes for the optimal placement of radar search equipment for the successful detection of enemy UAVs. The protection scheme is based on the determination of coordinates, movement speeds and trajectories of spatial movements of enemy aircraft by means of kinematic design. The established coordinates of enemy UAVs are reported to command posts equipped with liquidator drones (kamikaze) and small arms or to control points of anti-aircraft missile systems (SAMS), which eliminate these aircraft. The improvement of radar search of moving objects by means of kinematic design is based on the introduction of additional search radar equipment and mathematical apparatus for precise calculations of coordinates and parameters of spatial movements of moving objects. Two paired radar search systems, equipped with modern high-speed computing equipment with appropriate software, are able to "screen out" false return electromagnetic signals. This makes it possible to clearly single out the wanted moving object and subsequently track its movement in space. For calculations of instantaneous coordinates and parameters of spatial movements of moving objects, appropriate mathematical dependencies are proposed, including for calculations of the distance of a moving object to radar stations, its coordinates in the introduced orthogonal coordinate system, speed and acceleration of movement, etc. All this will increase the effectiveness of detecting enemy strike and sabotage-reconnaissance unmanned aerial vehicles, including Iranian-made drones of the Sahed-136 model.